2018
DOI: 10.1175/jcli-d-17-0194.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Winter Ural Blocking on Arctic Sea Ice: Short-Time Variability

Abstract: Using daily reanalysis data from 1979 to 2015, this paper examines the impact of winter Ural blocking (UB) on winter Arctic sea ice concentration (SIC) change over the Barents and Kara Seas (BKS). A case study of the sea ice variability in the BKS in the 2015/16 and 2016/17 winters is first presented to establish a link between the BKS sea ice variability and UB events. Then the UB events are classified into quasi-stationary (QUB), westward-shifting (WUB), and eastward-shifting (EUB) UB types. It is found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 48 publications
11
57
0
Order By: Relevance
“…Such westward propagation of blocking during winter (link 7, Figure ) has been documented in previous studies. Chen et al () described cases of blocking anomalies with sufficient amplitude to propagate westward against the eastward flow (see also Luo et al, ; Yao et al, ). The weakening of the stratospheric polar vortex in November 2016 might have impacted the midlatitude wave guide on a hemispheric scale by weakening the westerly flow and allowing BE of the Urals to retrogress into Europe in December 2016 and January 2017.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such westward propagation of blocking during winter (link 7, Figure ) has been documented in previous studies. Chen et al () described cases of blocking anomalies with sufficient amplitude to propagate westward against the eastward flow (see also Luo et al, ; Yao et al, ). The weakening of the stratospheric polar vortex in November 2016 might have impacted the midlatitude wave guide on a hemispheric scale by weakening the westerly flow and allowing BE of the Urals to retrogress into Europe in December 2016 and January 2017.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In many studies UB is defined as blocking occurring over the sector 30-90 • E (e.g., Chen et al, 2018) or 40-80 • E (e.g., Gong & Luo, 2017;Luo et al, 2016a). However, often, the Ural sector is loosely defined and extends beyond the above mentioned domain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influences of blocking in the Ural region on the climate have been discussed. Chen et al () pointed out that quasi‐stationary Ural Blocking contributes to a reduction in the BKS sea ice. Our light‐ice composite also has a feature resembling Ural Blocking, for example, anticyclonic anomalies around the BKS (see Figure b).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies argued that the ice-albedo feedback is unimportant for recent winter Arctic warming, whereas the enhanced downward infrared radiation (IR) is more important for the winter Arctic warming and sea ice loss both on the intra-seasonal and interannual time scales (Doyle et al, 2011;Woods et al, 2013;Park et al, 2015;Woods and Caballero, 2016;. Furthermore, the enhanced water vapour injection from outside the Arctic was used to explain the intensified downward IR anomalies on the intra-seasonal or interannual time scales (Woods et al, 2013;Woods and Caballero, 2016;Luo et al, 2016a;Luo et al, 2016b;Chen et al, 2018;Zhong et al, 2018). In particular, Woods et al (2013) and Woods and Caballero (2016) found that the enhanced poleward moisture intrusion is often located on the western side of a blocking anticyclone.…”
mentioning
confidence: 99%